The relationship between ESG disclosure and corporate financial performance: a comparative study among developed and emerging markets companies - Liang, Yanni (Department of Finance and Tax, 2025)
This study examines the impact of companies' environmental, social and governance (ESG) disclosure on corporate financial performance. It also compares this relationship among developed and emerging markets companies. The study was based on ESG scores from data obtained from Bloomberg. The sample data consisted of information from 2145 developed and 2023 emerging companies from 2015 to 2022. Using a Fixed-Effects panel regression model, the research results indicate that developed market companies represent higher ESG combined and sub-component scores than emerging market companies. This study finds that developed market companies' ESG performance is positively associated with financial performance (ROA) and market valuation (Tobin's Q). Companies in emerging markets showed a positive relationship between ESG scores and market valuation (Tobin's Q). Results also indicated a neutral relationship between ESG initiatives and emerging markets companies' ROA. Thus, the study implies that ESG investment is still in the early stage in emerging markets with room for growth, while developed market ESG performance is leading the way in terms of its impact on company performance. The results indicate that whilst the market recognises the potential benefit of ESG investment, it still has some way to go regarding translation into the company's book performance. This has significant implications for investment decisions. This study fills an existing gap in literature in understanding the relationship between company performance and investment in ESG, especially as it pertains to the difference in this relationship between companies in emerging and developed economies.